Regioselectivity of glycosylation reactions of galactose acceptors: an experimental and theoretical study - del Vigo, Enrique Andres (2019)
Regioselective glycosylations allow planning simpler strategies for the synthesis of oligosaccharides, and thus reducing the need of using protecting groups. With the idea of gaining further understanding of such regioselectivity, we analyzed the relative reactivity of the OH-3 and OH-4 groups of 2,6-diprotected methyl α- and β-galactopyranoside derivatives in glycosylation reactions. The glycosyl acceptors were efficiently prepared by simple methodologies, and glycosyl donors with different reactivities were assessed. High regioselectivities were achieved in favor of the 1→3 products due to the equatorial orientation of the OH-3 group. A molecular modeling approach endorsed this general trend of favoring O-3 substitution, although it showed some failures to explain subtler factors governing the difference in regioselectivity between some of the acceptors. However, the Galp-(β1→3)-Galp linkage could be regioselectively installed by using some of the acceptors assayed herein.